EFFICACY OF AMIKACIN AND CIPROFLOXACIN AGAINST CLINICAL ISOLATES OF MYCOBACTERIUM TUBERCULOSIS - Satti, Masood; Faqir, Farah; Sattar, Abdul; Abbasi, Shahid; Butt, Tariq; Karamat, Karamat Ahmed; Abidi, Mubashir (Journal of Ayub Medical College Abbottabad, 2010)
Background: Tuberculosis was a leading cause of death at the turn of the 20th century and continues to be one of the medical scourges of mankind. Before the availability of antimicrobial drugs the cornerstone of treatment was rest in the open air in sanatoria. The major breakthrough in treatment of tuberculosis came with the discovery of Streptomycin. Later, INH, Ethambutol, Pyrazinamide, Rifampicin were added to the arsenal. Objective of this study was to determine the sensitivity of clinical isolates of Mycobacterium tuberculosis against two second-line anti-tuberculosis drugs, Amikacin and Ciprofloxacin. Methods: This cross-sectional study was conducted at Department of Microbiology, Armed Forces Institute of Pathology (AFIP) Rawalpindi. All routine clinical samples received for acid fast bacilli (AFB) in the Department of Microbiology, AFIP, Rawalpindi were processed by modified Petroff's technique and inoculated on Lowenstein Jensen (LJ) medium and Bactec 460 Mycobacterium tuberculosis culture system. After identification of M. tuberculosis sensitivity was performed against first-line anti-tuberculosis drugs. Then susceptibility of M. tuberculosis isolates against Amikacin and Ciprofloxacin was performed on LJ medium. H37Rv was used as control strain. Results: Results were interpreted using resistance ratio method. Out of 100 M. tuberculosis isolates, 98% were sensitive to Amikacin and 97% to Ciprofloxacin. Conclusion: Amikacin and Ciprofloxacin are very effective 2nd line anti-tuberculosis drugs against tuberculosis isolates in our set-up. Keywords: Tuberculosis, MDR-tuberculosis, susceptibility, second-line anti-tuberculosis drugs